Registration of 'Chisholm' Zoysiagrass. Issue 1 (10th October 2014) - Chandra, A.; Fry, J. D.; Engelke, M. C.; Genovesi, A. D.; Wherley, B. G.; Reinert, J. A.; Metz, S. P.; Zhang, Q.; Okeyo, D.
Abstract : 'Chisholm' (Reg. No. CV‐273, PI 666039) is a zoysiagrass ( Zoysia japonica Steud.) approved for release by Texas A&M AgriLife Research, Dallas, TX, and the Kansas Agricultural Experiment Station, Manhattan, KS. Chisholm is a clonal selection made in 1997 from a germplasm nursery established in 1983 in Dallas. It was originally evaluated under the designation TAES 4436 and included in the 2002 National Turfgrass Evaluation Program Zoysiagrass Variety Test under the designation DALZ 0102. Chisholm has a texture coarser than 'Meyer' and intermediate to 'JaMur' and 'Palisades'. Freezing tolerance of Chisholm is equivalent to, or slightly poorer than, Meyer, but it is superior to Meyer for establishment rate from vegetative plugs; turfgrass quality; growth under shade; fall color; resistance to bluegrass billbug ( Sphenophorus parvulus Gyllenhal), zoysiagrass mite ( Eriophyes zoysiae Baker, Kono, and O'Neill), and take all patch [caused by Gaeumannomyces graminis var. graminis (Sacc.) Arx & D.L. Olivier]; recovery from divots; and seed head production (fewer produced). Improvement over Meyer in these traits will potentially increase the utility of zoysiagrass in the transition zone. Chisholm is well suited for use on lawns and golf courses in the transition zone, particularly those areas in zones 6b or higher on the USDA Plant Hardiness Zone map.